Double-blind, placebo-controlled, proof-of-concept trial of bexarotene in moderate Alzheimer's disease. Issue 1 (December 2016) - Cummings, Jeffrey; Zhong, Kate; Kinney, Jefferson; Heaney, Chelcie; Moll-Tudla, Joanne; Joshi, Abhinay; Pontecorvo, Michael; Devous, Michael; Tang, Anne; Bena, James
Abstract Background We assessed the impact of retinoid X receptor (RXR) agonist bexarotene on brain amyloid measured by amyloid imaging in patients with Alzheimer's disease (AD) in a proof-of-concept trial. Methods Twenty patients with AD [Mini Mental State Examination (MMSE) score 10–20 inclusive] with positive florbetapir scans were randomized to receive 300 mg of bexarotene or placebo for 4 weeks. The amyloid imaging result was the primary outcome. Whole-population analyses and prespecified analyses by genotype [apolipoprotein E ε4 (ApoE4) carriers and ApoE4 noncarriers] were conducted. Secondary outcomes included scores on the Alzheimer's Disease Assessment Scale–Cognitive subscale, Alzheimer's Disease Cooperative Study–Activities of Daily Living scale, MMSE, Clinical Dementia Rating scale, and Neuropsychiatric Inventory. Serum amyloid-β (Aβ) peptide sequences Aβ1–40 and Aβ1–42 measurements were collected as biomarker outcomes. Results There was no change in the composite or regional amyloid burden when all patients were included in the analysis. ApoE4 noncarriers showed a significant reduction in brain amyloid on the composite measure in five of six regional measurements. No change in amyloid burden was observed in ApoE4 carriers. There was a significant association between increased serum Aβ1–42 and reductions in brain amyloid in ApoE4 noncarriers (not in carriers). There were significant elevations in serum triglycerides in bexarotene-treated patients. There was no consistent change in any clinical measure. Conclusions The primary outcome of this trial was negative. The data suggest that bexarotene reduced brain amyloid and increased serum Aβ1–42 in ApoE4 noncarriers. Elevated triglycerides could represent a cardiovascular risk, and bexarotene should not be administered outside a research setting. RXR agonists warrant further investigations as AD therapies. Trial registration ClinicalTrials.gov identifierNCT01782742 . Registered 29 January 2013.